Targetting of formyl-peptide receptor 1 (FPR1) and inflammasome pathways to modulate neutrophil and macrophage activity in inflammation - Fernando, M. Anuruddika J. (The University of Edinburgh, 2025)
Neutrophils and macrophages coordinate the initiation and resolution of inflammation, however, dysregulated or overactivation of their signalling pathways, particularly through pattern recognition receptors like formyl-peptide receptor 1 (FPR1) and NODlike receptors (NLRs) can contribute to acute and chronic inflammatory conditions. During infection or sterile injury, formylated peptides from pathogens (PAMPs) and tissue damage (DAMPs) engage FPR1 on leukocytes, mainly neutrophils, triggering their functions. They further activate Toll-like receptors (TLRs), which in turn stimulate intracellular NLRs, leading to the formation of NLRP1/NLRP3 inflammasome complexes. This process results in the release of pro-inflammatory cytokines and pyroptosis, further amplifying inflammation. Despite extensive preclinical research and clinical trials, effective therapies remain limited and therefore, characterizing these targets and inhibiting aberrant signalling with potential pharmaceutical inhibitors holds promise for developing novel anti-inflammatory agents that could be translated into clinical use for managing inflammation in many diseases. Our findings show that the established FPR1 antagonist, cyclosporin-H (CsH) effectively inhibits fMLF (N-Formylmethionine-leucyl-phenylalanine)-mediated neutrophil activation, including shape-change and key functions such as chemotaxis and ROS (reactive oxygen species) production. In contrast, the novel small molecule ADS051 does not act as a direct FPR1 antagonist but instead modulates FPR1 signalling, significantly suppressing human neutrophil shape-change and chemotaxis toward fMLF. These data were further supported by competition binding studies, where ADS051 failed to reduce the binding of fluorescently labelled formylated peptide to FPR1. Additionally, ADS051 did not inhibit neutrophil shape-change stimulated by other GPCRs including the Leukotriene B4 receptor (BLT1), CXC chemokine receptors (CXCRs), and platelet-activating factor receptor (PAFR), further confirming its specificity for FPR1 signalling. We further provide the first evidence that CsH administered every other day improves weight loss, reduces inflammation-induced pathology, and inhibits immune cell infiltration into the colon in a 7-day mouse model of 2%-DSS-induced colitis. Inflammasome activation by microbial and environmental stimuli play a significant role in inflammation by driving myeloid cell influx, cytokine release and pyroptotic cell death. Our data demonstrate that the novel small molecule inhibitor ADS032 targets and inhibits both NLRP1 and NLRP3 inflammasomes, suppressing pro-inflammatory IL-1β release, inflammasome complex formation, and cell cytotoxicity through LDH release in human macrophages. In contrast, a more established inflammasome inhibitor, MCC950, selectively inhibited NLRP3 and its downstream markers. Notably, we provide the first evidence that MCC950 improves weight loss, granuloma formation, and immune cell infiltration into the lung and bronchoalveolar lavage (BAL) in an acute mouse model of crystalline silica-induced lung injury. Furthermore, MCC950 reduced fibrotic lesions when administered at the initiation of fibrosis, however, repeated administration may be necessary to achieve a more pronounced effect in the later 29- and 56-day fibrosis models. Thus, exploring the pre-clinical effects of these potential inhibitors/modulators will highlight the importance of reducing, rather than completely eliminating inflammation, ultimately offering clinical benefits for patients in future studies.
Targeting of Formyl-Peptide Receptor 1 (FPR1) and Inflammasome pathways to modulate neutrophil and macrophage activity in inflammation
Keywords: neutrophils; macrophages; inflammation; FPR1; NLRs; inflammasomes; cyclosporin-H; fMLF; binding